Invasive alien species in Macaronesia - Silva, Luís (2008)
"[…]. As a consequence of all the geographic conditions and of historical events, the Canaries show the richest biodiversity. As an example, regarding endemic taxa, the Canaries have 524 vascular plants and 2768 arthropods (Martín Esquivel et al. 2005) while the Azores have 72 and 267, respectively (Borges et al. 2005) and the archipelagos of Madeira and Selvagens altogether have 154 and 979 (Borges et al. 2008a) respectively. It is well known that there are several plant genera in the Canaries with high numbers of species (Aeonium, Echium, Argyranthemum, Sonchus, etc.), which probably resulted from adaptive radiation, while in the Azores endemic plant species are found at a rate of one, and more rarely two or three species per genus. An intermediate situation is found in Madeira where genera Argyranthemum (Asteraceae) and Sinapidendron (Brassicaceae) show six endemic taxa (Jardim & Sequeira 2008). There are also other significant differences among the archipelagos. For instance, regarding vertebrate taxa, in the Azores there are no native species of reptiles and there are only two native mammal species, two bats, one of which endemic (Nyctalus azoreum), while there are several species in those groups both in the Canaries and in Madeira, namely the small lizard from Madeira (Teira dugesii, with four subspecies) or the giant lizards from La Gomera (Gallotia bravoana), El Hierro (G. simonyi), Tenerife (G. intermedia) and Gran Canaria (G. stehlini), among others. Thus, although there are similarities among the different regions, important geographic differences dictated that the native flora and fauna would show striking differences among the archipelagos. This is of considerable importance in order to understand what happened in each region, regarding the introduction of alien species. For instance, it is usually accepted that several species of Mediterranean distribution are considered as native in Madeira or in the Canaries, while the same species are considered as alien in the Azores."